Penekanan Susut Non-Teknis dengan cara Optimalisasi Pelaksanaan P2TL di PT-PLN-(Persero)-ULP-Indarung - Arieyansyah Arieyansyah; Riki Mukhaiyar (Ranah Research : Journal of Multidisciplinary Research and Development, 2021)
Loss is the amount of energy lost in the process of distributing electrical energy from the substation to the consumer. PT PLN (Persero) ULP Indarung's losses in semester 1 of 2020 were still quite high with a total of 10,314,804 kWh, while non-technical losses contributed 30.76% kWh of the total or equal to 3,173,508 kWh. Subscription Data Needs Attention (DLPD) to obtain Operational Targets (SO) and Operational Targets (TO), establish good communication with internal (Outsourcing) and External (community) parties to obtain accurate Operational Targets (TO), and implement P2TL SOPs in the field. After P2TL optimization efforts were made, the total losses in semester 1 of 2021 were 8,108,489 kWh, while non-technical losses in semester 1 of 2021 contributed 4.03% of the total or equal to 326,762 kWh. Therefore the P2TL optimization effort is said to be successful because it can reduce non-technical losses from 3,173,804 kWh to 326,762 kWh, with P2TL itself contributing 2,020,376 kWh.